Absolute Pitch and Its Frequency Range - Andrzej RAKOWSKI; Piotr ROGOWSKI (Archives of Acoustics, 2013)
This paper has two distinct parts. Section 1 includes general discussion of the phenomenon of “absolute pitch” (AP), and presentation of various concepts concerning definitions of “full”, “partial” and “pseudo” AP. Sections 2–4 include presentation of the experiment concerning frequency range in which absolute pitch appears, and discussion of the experimental results. The experiment was performed with participation of 9 AP experts selected from the population of 250 music students as best scoring in the pitch-naming piano-tone screening tests. Each subject had to recognize chromas of 108 pure tones representing the chromatic musical scale of nine octaves from E0 to D#9. The series of 108 tones was presented to each subject 60 times in random order, diotically, with loudness level about 65 phon. Percentage of correct recognitions (PC) for each tone was computed. The frequency range for the existence of absolute pitch in pure tones, perceived by sensitive AP possessors stretches usually over 5 octaves from about 130.6 Hz (C3) to about 3.951 Hz (B7). However, it was noted that in a single case, the upper boundary of AP was 9.397 Hz (D9). The split-halves method was applied to estimate the reliability of the obtained results.